Regional Integration and Economic Growth: New Empirical Evidence from the East African Community. Issue 4 (4th July 2021) - Ejones, Francis; Agbola, Frank W.; Mahmood, Amir
ABSTRACT: This article empirically investigates the impact of the East African Community (EAC) on economic growth. We utilized a comprehensive panel data spanning from 1988 to 2017. We estimated an endogenous growth model using feasible generalized least squares (FGLS) and panel corrected standard error (PCSE) estimators. Regional trade agreements (RTAs) and trade openness enhance economic growth. RTAs in the same region have a more significant impact on economic growth than plurilateral and multilateral RTAs. Regionalism in the EAC has heterogeneous country effects on economic growth. Our results are robust to alternative model specifications, highlighting the importance of RTAs in enhancing economic growth.